A 14‐ka record of dust input and phytoplankton regime changes in the subtropical NE pacific: oceanic and terrestrial processes linked by teleconnections at suborbital scales (2019)
We study shifts in phytoplankton proxies linked to terrigenous inputs and teleconnections in a core from Soledad Basin, Gulf of Ulloa, NW Mexico, spanning the end of the deglaciation and the Holocene. We used biogenic opal (% opal), organic carbon (% total organic carbon [TOC]), and inorganic carbon (% CaCO3) as proxies of productivity and opal/TOC and CaCO3/TOC ratios as proxies of nutrient uptake and C‐export by siliceous and carbonate organisms. We reconstructed terrestrial inputs and identified authigenic gypsum. Based on opal/TOC and CaCO3/TOC ratios, we found periodic changes of ~0.5, 1.1–1.8 ka cycle in phytoplankton proxies exporting siliceous and carbonate skeletal debris to the sediments. An increase in carbonate organisms occurred during 14–8.7 ka, corresponding to reduced El Niño–Southern Oscillation (ENSO)‐like variability, in parallel to the northward displacement of the Intertropical Convergence Zone (ITCZ) and an overall negative phase of the Pacific Decadal Oscillation (PDO). An increase in siliceous organisms occurred between 6 and 3 ka, coincident with strong ENSO‐like conditions, southern migration of ITCZ, and less intense but more frequent positive PDO‐hydrological variability. Grain size analyses show significant amounts of fine fraction (dust <6.6 μm) present during the early‐ to mid‐Holocene in agreement to extreme weather on land, with episodes of eolian and fluvial transport to the sea. The ENSO‐like variations influenced biological C‐export producers on a scale of 1.1–1.8 ka, but PDO‐related variability is uncertain. We suggest that Holocene drivers for phytoplankton successions are changes in insolation, ITCZ migration, California Current upwelling, nutrient inputs by advection, and terrestrial sources.